2021
DOI: 10.1371/journal.pone.0251246
|View full text |Cite
|
Sign up to set email alerts
|

Prospective estimation of the age of initiation of cigarettes among young adults (18–24 years old): Findings from the Population Assessment of Tobacco and Health (PATH) waves 1–4 (2013–2017)

Abstract: Objectives To prospectively estimate the age of cigarette initiation among young adults (18–24 years old) who were never cigarette users at their first wave of adult study participation overall, by sex, and by race/ethnicity given recent increases in cigarette initiation occurring in young adulthood. Methods Secondary analyses were conducted using the PATH restricted-use adult datasets among young adult never users of cigarettes in waves 1–3 (2013–2016) with outcomes followed-up in waves 2–4 (2014–2017). Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
(116 reference statements)
0
8
1
Order By: Relevance
“…Tobacco Use Insights n n tobacco products other than cigarettes is increasing in young adults. [4][5][6][7][8][9]55 Our results stand in contrast to previous research regarding the particular products that exhibited sex differences in the age of susceptibility onset. Specifically, a previous nationally representative sample of young adults (18-24 years old) found that males had increased prevalence of susceptibility to cigarette use compared with females (25.6% and 14.1%, respectively), 24 while we found no differences in the age of susceptibility onset between males and females.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Tobacco Use Insights n n tobacco products other than cigarettes is increasing in young adults. [4][5][6][7][8][9]55 Our results stand in contrast to previous research regarding the particular products that exhibited sex differences in the age of susceptibility onset. Specifically, a previous nationally representative sample of young adults (18-24 years old) found that males had increased prevalence of susceptibility to cigarette use compared with females (25.6% and 14.1%, respectively), 24 while we found no differences in the age of susceptibility onset between males and females.…”
contrasting
confidence: 99%
“…However, these campaigns are typically targeted toward youth instead of young adults, 3 despite the fact that an increasing amount of tobacco product initiation occurs during young adulthood. [4][5][6][7][8][9] Thus, identifying the age at which young adults become susceptible to tobacco product use is critical for prevention efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have underlined the importance of age of first smoking as a predictor of smoking persistence. The high persistence of smoking in young adults begins as teenagers when they first try and has become a problem for millions of young adults today 21 . This study found that young males who first tried smoking as adolescents were influenced by their closest friends who smoked and shared their habits.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use remains high among youth and young adults despite recent efforts to curb tobacco initiation in the context of the evolving tobacco product landscape [1][2][3][4][5][6][7] . A recent report of the 2021 National Youth Tobacco Survey (NYTS) indicated that 19.4%, 8.1% and 2.8% of middle and high school students, had ever used e-cigarettes, cigarettes, and hookah, respectively 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding longitudinal patterns of tobacco use behaviors is central to curbing tobacco initiation, as this information can identify windows of opportunity in which to intervene to prevent or reduce progression in the severity or intensity of tobacco use [2][3][4][5][6][7] . This is particularly important among never users of a particular TP who may be susceptible to initiation of a particular TP and later on progress to regular TP use.…”
Section: Introductionmentioning
confidence: 99%